2021
DOI: 10.1007/s13555-021-00492-1
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Corticosteroid-Induced Rosacea-Like Dermatitis with Platelet-Rich Plasma Mesotherapy: Report of Seven Cases

Abstract: Introduction Corticosteroid-induced rosacea-like dermatitis (CIRD) is one of the cutaneous side effects of long and excessive application of topical corticosteroids, resembling rosacea that can present with a series of cutaneous manifestations. Most patients with CIRD undergo a variety of long-term treatments before their symptoms are relieved as there is no accepted standard therapy. We gave each of seven patients two sessions of platelet-rich plasma (PRP) mesotherapy before the routine treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Day-60 in one study. 1 One study also demonstrated that after a single PRP injection on the cheeks, majority of the patients were significantly satisfied on FACE-Q post care scales whereas according to GIAS score, 14 (45.1%) patients had esthetic improvement. 18 Histopathological analysis has also demonstrated increase in collagen density within the dermis and subcutaneous layer after PRP treatment.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Day-60 in one study. 1 One study also demonstrated that after a single PRP injection on the cheeks, majority of the patients were significantly satisfied on FACE-Q post care scales whereas according to GIAS score, 14 (45.1%) patients had esthetic improvement. 18 Histopathological analysis has also demonstrated increase in collagen density within the dermis and subcutaneous layer after PRP treatment.…”
Section: Discussionmentioning
confidence: 98%
“…PRP has been successfully used in the treatment of corticosteroid‐induced rosacea like dermatitis with about 71.4% patients reporting improvement at Day‐30 and in 100% patients at Day‐60 in one study 1 . One study also demonstrated that after a single PRP injection on the cheeks, majority of the patients were significantly satisfied on FACE‐Q post care scales whereas according to GIAS score, 14 (45.1%) patients had esthetic improvement 18 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Compared to conventional oral drugs, it has fewer systemic side effects and can administer pharmaceuticals directly to damaged tissues, improving efficacy. Furthermore, mesotherapy has shown promise in the management of alopecia and cellulite, among other dermatological issues [ 6 ].…”
Section: Introductionmentioning
confidence: 99%